Reliability and accuracy of intraoral radiography, cone beam CT, and dental MRI for evaluation of peri-implant bone lesions at zirconia implants: an ex vivo feasibility study - Miotk, Nikolai; Schwindling, Franz Sebastian; Zidan, Mousa; Jürchott, Alexander; Rammelsberg, Peter; Hosseini, Zahra; Nittka, Mathias; Heiland, Sabine; Bendszus, Martin; Hilgenfeld, Tim (Journal of dentistry, 2023)
Objectives - To determine the reliability and accuracy of intraoral radiography (IR), cone-beam-computed tomography (CBCT), and dental magnetic resonance imaging (dMRI) in measuring peri‑implant bone defects around single zirconia implants. - Methods - Twenty-four zirconia implants were inserted in bovine ribs with various peri‑implant defect sizes and morphologies. True defect extent was measured without implant in CBCT. Defects were measured twice in IR, CBCT, and dMRI with the inserted implant by three experienced readers. Reliability was assessed by ICC, accuracy by the Friedman test, and post-hoc-Tukey's test. - Results - A comparable good to excellent intra- and inter-reader reliability was observed for all modalities (intra-/inter-rater-CC range for IR; CBCT; dMRI: 0.81-0.91/0.79;0.87-0.97/0.96;0.87-0.95/0.94). Accuracy was generally high, with mean errors below 1 mm in all directions. However, measuring defect depth in the mesiodistal direction was significantly more accurate in dMRI (0.65 ± 0.38 mm) compared to IR (2.71 ± 1.91 mm), and CBCT (1.98 ± 1.97 mm), p-values ≤ 0.0001 respectively ≤ 0.01. - Conclusions - Osseous defects around zirconia implants can be reliably measured in IR/CBCT/dMRI in the mesiodistal directions. In addition, CBCT and dMRI allow assessment of the buccolingual directions. dMRI provides a comparable accuracy in all directions, except for the mesiodistal defect depth, where it outperforms IR and CBCT.